PENGARUH PENDIDIKAN GIZI TENTANG POLA MAKAN SEIMBANG MELALUI GAME PUZZLE TERHADAP PENINGKATAN PENGETAHUAN ANAK SDN 067690 KOTA MEDAN - Athira Demitri; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Balanced diet on elementary student are rarely fulfilled. They tend to only eat foods with few nutrients dominant, such as burgers are high in carbohydrates and fats that can cause obesity. With the existence of such problems, nutrition education made by interested media to facilitate the provision of nutritional information, in particular a balanced diet. The aim of this research is to find out the effect of nutrition education about balanced diet through puzzle game to increase the knowledge of elementary student of SDN 067690 in Medan. The type of this research is quasi experimental with one group pretest posttest design. Total population is 249 children and the number of samples is 45 children. Analysis of data using statistical test of paired t-test, the significant level of 95%. The results showed that children given knowledge puzzle game with pretest scores of elementary student in low category (26.7%) and posttest scores in low category (0.0%). Statistical analysis showed there were differences in knowledge scores after nutrition education through puzzle game (p.= 0,000). The conclusion of this research is there were the effect of nutrition education through puzzle game for the elementary student’s knowledge about balanced diet, which is an increase of elementary student’s knowledge about balanced diet. Suggestions of this research was to implementing the nutrition workers in community health centers to use puzzle game to inform about balanced diet. Keywords: balanced diet knowledge, puzzle game, elementary student